Productivity Analysis of Tree-Length Harvesting using Farm Tractor in a Nordmann Fir Stand in Turkey - CAGLAR, Sadik (European Journal of Forest Engineering, 2020)
Because of the low investment costs, the winch equipped farm tractors usage is the most common logging technique for the primer transportation of wood-based forest products in Turkey. During the logging operations, farm tractors are commonly used for cable winching at a steep terrain while they are used for skidding operation on relatively flat terrain conditions in forest stands. The aim of this study was to evaluate the working conditions and determine the productivity of uphill winching using a farm tractor during tree length harvesting operation in a Nordmann fir stand (Abies nordmanniana). The study was conducted in Western Black Sea Region of Turkey. The average diameter and length of the forest products which were hauled from stump-site to landing areas were 17 cm and 28 m, respectively. The winching distances were ranged from 10 m to 70 m. Time analysis and field measurements related to independent variables (including winching distance, tree diameter, length and volume) were conducted while the farm tractor was winching the harvested forest products. For the farm tractor, the productivity was estimated and the cycle time prediction model was developed using the multiple regression method. It was found that the average hourly and daily productivity were 5.80 m3/hour and 46.42 m3/day for 8 hours, respectively. The most time consuming work element was winching (49.2%), followed with delay time (20.1%).
Keywords: Engineering; Mühendislik; Forest harvesting; Farm tractor; Winching; Productivity; 15. Life on land